Polarity-Dependent Dielectric Behavior of XLPO-Insulated PV Cables Under High-Voltage AC and DC Stress: Leakage Current and PRPD Analysis - Khomsan Ruangwong; Norasage Pattanadech; Pittaya Pannil (My University, 2025)
This study investigates the dielectric behavior of cross-linked halogen-free polyolefin (XLPO) insulation in H1Z2Z2-K photovoltaic cables under a direct current (DC) stress of $\pm 999.6 ~\mathrm{V}$. The results indicate significant polarity-dependent responses, with insulation resistance (IR) rising from $1.61 ~\mathrm{T} \Omega$ under negative DC to $2.30 ~\mathrm{T} \Omega$ under positive DC. Furthermore, the polarization index (PI) and dielectric absorption ratio (DAR) improve from 6.73 and 2.14 to 12.78 and 2.43, respectively. The Loss Index, obtained from polarization-depolarization current (PDC) analysis, increases from 0.935 to 0.991, suggesting enhanced dielectric stability with positive bias. Additionally, the partial discharge inception and extinction voltages (PDIV and PDEV) are recorded at 8.3 kV for DC and 1.93 kV for AC, exhibiting symmetrical behavior that indicates corona and surface discharge dominance and minimal space charge retention. These findings highlight the importance of considering space charge dynamics and polarity-aware diagnostics in evaluating non-certified XLPO-insulated cables in photovoltaic applications.
Keywords: High voltage insulation and dielectric phenomena; Power Transformer Diagnostics and Insulation; Dielectric materials and actuators